Swear Words Used by Filipino: A Case Study - Wiguna, Ida Bagus Andika; Budasi, I Gede; Paramarta, I Made Suta (Universitas Pamulang, 2025)
This study was designed using descriptive qualitative method that aims to identify and to analyze the forms, the functions, and the references of swear words in the Filipino language. Primary data in this research was collected using in-depth interview techniques, while secondary was collected by doing document analysis. The researcher acted as the main instrument which was equipped with additional instrument in the form of an interview guide, questionnaire by choosing three informants who were selected based on predetermined criteria. The Data were collected from Filipino tourists visiting Bali. The research found a total of 54 swear words in Filipino, classified across various categories. In terms of form, swear words appear as words (23), phrases (12), and clauses (19). For the function of the function swear words, they serve to expressing emotions (10), drawing attention (3), aggression and provocation (47), and have regressive uses (38). Furthermore, the study analyzed the references underlying these swear words, identifying categories such as religion (6), sex (6), excrement (3), animal names (7), mental illness (19), and personal background (8). These findings answer all research questions set previously where it can contribute to a deeper understanding of the multifaceted nature of swear words in Filipino and highlight the potential for cross-cultural misunderstandings if not carefully considered. it has significant implications in the field of sociolinguistics, particularly in understanding the structure, function, and sociocultural references of swear words in the Filipino language. In addition, this study has practical implications for intercultural communication, especially for individuals interacting with Filipinos in various contexts, such as tourism, business, and social settings.